Dem Herrgott sei Scheenster. On dative-marked nominal possessive constructions in East Franconian. - Nickel, Grit (Non-Central Usages of Datives, 2016)
By integrating dialect data into typological theses on dative-marked nominal possessive constructions of the type dem Vater sein Hut, this article will continue recent approaches of both dialectological and typological research. By means of an empirical study, this article intends to not only describe the surface phenomena, but to uncover the underlying structure of this construction in East Franconian dialects. Language maps illustrate that instances of microvariation concerning the case-marking of the possessor (Wem vs. Wen vs. Wer seine Weiden sind das?) and the form of the possessive pronoun (meiner Tante ihr vs. sein Wirsing) are diatopically conditioned.
Keywords: prenominal dative case-marking; possessive constructions; dialect data; morphosyntactic microvariation; syntactic doubling

Von Gäul-s-bauer, April-s-narr und Getreid-s-gabel. Die Verwendung und Verbreitung des Fugen-s im Ostfränkischen. - Nickel, Grit (Wortbildung im Deutschen. Aktuelle Perspektiven., 2016)
This article addresses the linking element -s- concerning its distribution and functionality in  dialect German. Recent research has increasingly apprehended the system of linking elements in standard German. These systematical and functional aspects are introduced first. By means of an empirical study of lexicalized nominal compounds, this paper then examines the variation of the linking element -s- and zero linking element as well as other types of compositional stem forms (Gäul-s-bauer, Vögel-s-beere, April-a-narr) in the East Franconian dialect. We show that the distribution of linking elements in our study area is not only based on functional aspects, such as morphological complexity (Getreid-s-gabel vs. Treid-ø-gabel), but on diatopical preference as well. Language maps illustrate that the linking-s is more frequent in the northern part of our study area.
Keywords: Fugenelemente; dialektale Morphologie; Ostfränkisch